2021
DOI: 10.3389/fpsyt.2021.743526
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated With Increased Adolescent Non-suicidal Self-Injury During the COVID-19 Pandemic

Abstract: Non-suicidal self-injury (NSSI) in adolescents hospitalized with psychiatric disorders continues to increase after the outbreak of COVID-19. This study aimed to explore the relationship between the pandemic and NSSI among adolescents and whether the composition of psychosocial factors related to NSSI has changed during the pandemic. Through the retrospective analysis of medical records retrieved from the electronic system of the psychiatric hospital located in Chengdu from January 2016 to March 2021, 609 medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
(51 reference statements)
3
17
0
Order By: Relevance
“…Our study represents one of few studies that deepen interactive-relational characteristics of NSSI adolescents before the pandemic period. As confirmed by recent studies, non-suicidal self-injury in adolescents has significantly increased after the outbreak of COVID-19 [ 45 , 46 ] and worse family and parent-children relationships appear strongly related as predisposing factors [ 47 ].…”
Section: Discussionmentioning
confidence: 88%
“…Our study represents one of few studies that deepen interactive-relational characteristics of NSSI adolescents before the pandemic period. As confirmed by recent studies, non-suicidal self-injury in adolescents has significantly increased after the outbreak of COVID-19 [ 45 , 46 ] and worse family and parent-children relationships appear strongly related as predisposing factors [ 47 ].…”
Section: Discussionmentioning
confidence: 88%
“…Most of the studies reported that the stress that children and adolescents have been subjected to, due to school closures and social distancing during the pandemic, impacted their mental health producing negative and different side effects ( 20 23 ), depending on their age, gender, ethnicity, family circumstances, socioeconomic situation ( 22 , 24 ). Greater negative effects on any pre-existing mental health problem ( 25 ) and heavier mental health outcomes were found in those who already had poor mental health before the COVID-19 pandemic ( 26 , 27 ). Furthermore, countries' health outcomes were influenced by local political decisions and media intervention, following public reactions, allowing for a major difference in morbidity and mortality within and between countries.…”
Section: A Syndemicmentioning
confidence: 99%
“…In contrast, during the COVID-19 outbreak (February 28 to March 11, 2020), data from the Taiwan Province of China found that the prevalence of NSSI among junior high school students was 40.9% ( 12 ). Simultaneously, the proportion of NSSI among hospitalized adolescents with mental disorders in China has increased from 29.2% in 2016 to 92.5% in 2020 and 95.9% in 2021 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%